Detection of preclinical motor neurone loss in SOD1 mutation carriers using motor unit number estimation. Issue 2 (1st August 2002) - Aggarwal, A; Nicholson, G
Abstract : Objective: To determine the pattern of motor neurone loss in amyotrophic lateral sclerosis (ALS). In particular, to determine whether there is a gradual life long presymptomatic motor neurone loss or, alternatively, a sudden catastrophic loss just before the onset of symptoms. Method: The statistical motor unit number estimation (MUNE) technique was used in a longitudinal study of 19 asymptomatic carriers of the Cu, Zn superoxide dismutase 1 (SOD1) gene. MUNE results were compared with those of 34 age and sex matched SOD1 negative family controls and 23 population controls. Motor neurone loss was also estimated in 12 patients with sporadic ALS. 84 subjects (43 male and 41 female patients) with an age range from 16–73 years were followed up over three years, both clinically and by MUNE, every six months. Results: In 2 of the 19 mutation carriers, there was a sudden reduction in MUNE several months before the onset of weakness. The patients with symptomatic sporadic ALS also had a reduced MUNE, but there was no detectable loss of motor neurones in the remainder of the subjects. Conclusion: MUNE can be used to detect preclinical loss of motor units in familial ALS. Normal numbers of motor neurones were maintained in 17 SOD1 mutation carriers over the three year period. There was an abrupt loss of motor neurones just before the onset of symptomatic weakness in two SOD1 mutation carriers. These results suggest that some form of trigger may initiate rapid cell loss and death of motor neurones just before the onset of symptoms.